β-carotene production by Sporobolomyces pararoseus TISTR5213 using crude glycerol as the sole carbon source - Manowattana,A. (Chiang Mai University, 2015)
© 2015, Chiang Mai University. All rights reserved. Recycling crude glycerol obtained from biodiesel production process has challenges, particularly as this glycerol is not suitable for foods and cosmetics applications. Therefore, nine strains of red yeasts from the culture collection of the Thailand Institute of Scientific and Technological Research (TISTR) were screened for β-carotene production in the basal medium supplemented with either pure glycerol (BMP) or crude glycerol (BMC) as the sole carbon source. The results revealed that Sporobolomyces pararoseus TISTR5213 showed the maximum β-carotene production yield of 0.62±0.05 and 1.17±0.01 mg/L in BMP and BMC, respectively. Variable medium components of BMC were selected in accordance with the Plackett-Burman experimental design with only one factor of crude glycerol being significant. The optimal conditions for physical factors (pH and temperature levels) were then combined in further studies through the response surface methodology approach. A quadratic model was constructed by central composite design (CCD). Using this experimental design, the β-carotene production yield increased from 1.17 to 27.41 mg/L or about 23 times higher than non-optimized BMC. The optimal conditions to achieve the maximum β-carotene yield were; crude glycerol 55.04 g/L, initial pH at 5.63 and 24.01°C for 5 days.